2016
DOI: 10.1097/yct.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Safety of Electroconvulsive Therapy Use During the First Trimester of Pregnancy

Abstract: Although the data are limited, they suggest that ECT is relatively safe when administered during the first trimester of pregnancy. The possible adverse consequences of ECT during the first trimester of pregnancy should be carefully weighed against the potential benefits of ECT on untreated mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“…Another aspect to consider is that the studies in this review have generally included unselected ECT populations encompassing young and old, as well as those with or without somatic comorbidities. It is therefore worth noting that ECT is generally also considered to be safe in adolescents , the elderly , the pregnant , and individuals with cardiovascular disease , pulmonary disease , and intracranial masses .…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect to consider is that the studies in this review have generally included unselected ECT populations encompassing young and old, as well as those with or without somatic comorbidities. It is therefore worth noting that ECT is generally also considered to be safe in adolescents , the elderly , the pregnant , and individuals with cardiovascular disease , pulmonary disease , and intracranial masses .…”
Section: Discussionmentioning
confidence: 99%
“…There have been five systematic reviews of the safety of ECT in pregnancy since 2015 (Calaway et al, 2016; Coshal et al, 2019; Leiknes et al, 2015; Sinha et al, 2017; Spodniakova et al, 2015), with Calaway et al, focusing on the safety of ECT in the first trimester. These overlapping reviews examined several hundred case reports and concluded that ECT in pregnancy was relatively safe.…”
Section: Treatmentsmentioning
confidence: 99%
“…The authors of a meta-review listed fetal bradycardia/arrhythmia, premature birth, development delay, abdominal pain, uterine contraction, vaginal bleeding, placental abruption as the most frequent events that occurred when treating pregnant patients with ECT, but after analyzing the available data, they ended up supporting the fact that the administration of ECT in pregnancy is relatively safe (92). The same conclusion was drawn after research activity on ECT used in the first trimester of pregnancy, when only 1 patient out of 32 experienced a threatened abortion (93).…”
Section: Electroconvulsive Therapy (Ect)mentioning
confidence: 87%